Sistem Kendali Navigasi Quadcopter Menggunakan Suara Melalui Smartphone dan Arduino dengan Metode Text Processing - Faviansyah Arianda Pallas; Gembong Edhi Setyawan; Barlian Henryranu Prasetio (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Quadcopter categorized as flying robot that has four motors and four propelers each side. Remote control requires to navigate quadcopter, so special skill and experience needed to navigate it well. Based on that problem, we developed a control system using sound through smartphone and Arduino with text processing method. Incoming sound from user converted into text, and then each text splitted into words. Each word will be matched into database that has been created before, using stopword removal wordlist algorithm. The results will be sent to Arduino to do data processing becoming quadcopter movement. In this research using parrot Parrot Ar Drone 2.0 as quadcopter. From testing result, this system has 100% value at functional testing and user input processing. At quadcopter precision movement testing, accuracy of this system reach 89.3%. At application performance testing, this system average time for sound processing increase Â±1 second and average time for text preprocessing Â±300 nanosecond along with the increase of words. At quadcopter fliying performance, taken quadcopter angel value of Roll, Pitch, and Yaw within -180 O to +180 O. While minimum value of height is 0.062 meter and maximum height is 3 meter.